Spinocerebellar Ataxia Type 2 Is Associated with the Extracellular Loss of Superoxide Dismutase but Not Catalase Activity - Almaguer-Gotay, Dennis; Almaguer-Mederos, Luis E.; Aguilera-Rodríguez, Raul; Rodríguez-Labrada, Roberto; Cuello-Almarales, Dany; Estupiñán-Domínguez, Annelié; Velázquez-Pérez, Luis C.; González-Zaldívar, Yanetza; Vázquez-Mojena, Yaimé (Frontiers in Neurology, 2017)
Background: Spinocerebellar Ataxia type 2 (SCA2) is an inherited and still incurable neurodegenerative disorder. Evidence suggests that pro-oxidant agents as well as factors involved in antioxidant cellular defenses are part of SCA2 physiopathology. Aim: To assess the influence of superoxide dismutase (SOD3) and catalase (CAT) enzymatic activities on the SCA2 syndrome. Method: Clinical, molecular and electrophysiological variables, as well as SOD3 and CAT enzymatic activities were evaluated in 97 SCA2 patients and in 64 age and sex matched control individuals. Results: SCA2 patients had significantly lower SOD3 enzymatic activity than the control group. However, there were no differences between patients and controls for CAT enzymatic activity. The effect size for the loss of patients’ SOD3 enzymatic activity was 0.342, corresponding to a moderate effect. SOD3 and CAT enzymatic activities were not associated with the CAG repeat number at the ATXN2 gene. SOD3 and CAT enzymatic activities did not show significant associations with the age at onset, severity score or the studied electrophysiological markers. Conclusion: There is a reduced SOD3 enzymatic activity in SCA2 patients with no repercussion on the clinical phenotype.